An integrated investigation of the Rio tailings, Panasqueira mine, Centre Portugal - Grangeia, Carlos (2010)
The risks associated with mine tailings have different nature and, thus, only a multiple approach can investigate and monitor comprehensively the characteristics and evolution of mine tailings impacts on the environment. Deposition at the Rio tailings (Panasqueira Mine) lasted about ninety years. Over one million cubic metres, of complex very fine to fine material, are deposited on a mountain side overlaying the Zezere river, increasing the risk of contamination of one of the most important hydrographic basins in central Portugal. Herein, a multidisciplinary study including geophysics, geochemistry and borehole information, organized in a GIS, is used to characterize the Rio tailings. The geophysical survey comprised ERT (Electrical Resistivity Tomography) and GPR (Ground Penetrating Radar) on the mud impoundment, as well as, on the slope of the tailings. The geochemical survey consisted on collecting water and tailings samples, iron coatings, arsenopyrite stockpile material and ferruginous crust. Samples collected in boreholes, drilled specifically for this project, were also analyzed. The GIS provided imaging of the geophysical, geochemical and particle size spatial distribution, so that comparisons between the different data sets are easily done. Resistivity and GPR allowed bedrock positioning. GPR was able to give layering results within the tailings. Finally, comparison and correlation between geophysical and geochemical results are carried out and evaluated on the GIS platform.